Mapping local defects in PbO-based piezoceramics - Dimitriu, E.; Ramer, R.; Craciun, F. (Journal of crystal growth, 2011)
The effect of impurities and defects of various types on the properties of ferroelectric perovskites remains a subject of great interest and is investigated by increasingly sophisticated experimental techniques. The microscopic structure and defect chemistry of ferroelectric lead titanate ceramics with complex compositions (doped with Mn, Pr, Nd and Gd) prepared by standard solid-state oxide method were investigated in this study. Phase formation and microstructure were examined by XRD and SEM, respectively. Grains with unusual shapes and sizes are observed in a homogeneous matrix. Agglomerations of chemical components randomly distributed in the samples are revealed using the energy dispersive X-ray analysis with the microprobe technique and the elemental distribution within bulk ceramics is profiled. At least two oxidation states of the titanium and manganese ions are evidenced from optical reflection spectra. All observed local defects in the ferroelectric ceramic depended on the composition, the sintering temperature and the annealing conditions, and affected the conductivity and the dielectric and piezoelectric properties.